2018
DOI: 10.1007/s12119-018-9560-0
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Study of Same-Sex Kissing Among College-Attending Heterosexual Men in the U.S.

Abstract: This is the first research to assess the prevalence of same-sex kissing among collegeattending, heterosexual men in the United States. We utilized a mixed-method study of 442 quantitative surveys and 75 in-depth interviews with participants from 11 universities in order to understand the frequency, context and meanings of same-sex kissing. We found that the prevalence of kissing on the cheek among these participants was 40%, and kissing on the lips 10%. Both types of kisses were predicted by positive attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…However, a previous cross-sectional survey from Melbourne, Australia, among 2351 heterosexual men in 2016–2017 showed 76.1% of men had kissing-only partners in the previous three months [ 31 ], a slightly higher proportion than our study (65.5% of men had kissing-only partners). Our finding that women were significantly more likely than men to have same-sex kissing partners may reflect the stigmatisation of same-sex kissing among heterosexual men [ 32 ]. A mixed-methods study of heterosexual college students in the United States in 2018 found that of 517 heterosexual men, 10% reported ever kissing another man on the lips [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous cross-sectional survey from Melbourne, Australia, among 2351 heterosexual men in 2016–2017 showed 76.1% of men had kissing-only partners in the previous three months [ 31 ], a slightly higher proportion than our study (65.5% of men had kissing-only partners). Our finding that women were significantly more likely than men to have same-sex kissing partners may reflect the stigmatisation of same-sex kissing among heterosexual men [ 32 ]. A mixed-methods study of heterosexual college students in the United States in 2018 found that of 517 heterosexual men, 10% reported ever kissing another man on the lips [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that women were significantly more likely than men to have same-sex kissing partners may reflect the stigmatisation of same-sex kissing among heterosexual men [ 32 ]. A mixed-methods study of heterosexual college students in the United States in 2018 found that of 517 heterosexual men, 10% reported ever kissing another man on the lips [ 32 ]. This is lower than the estimate in our study showing only 3.9% of men kissed another man, and this is likely because we specifically asked participants to report ‘tongue kissing’, which may be more sexual than simply kissing on the lips, as the US study indicated most respondents who had same-sex kissing on the mouth indicated it was not romantic.…”
Section: Discussionmentioning
confidence: 99%
“…The global theme of physicality refers to the participants demonstrating increased levels of intentional touching. Fourteen studies (42.4%) reported this theme; however, it was more evident in sporting settings (Adams, 2011;Anderson, 2011;Anderson & McCormack, 2015;Morales & Caffyn-Parsons, 2017;Roberts et al, 2017) and educational settings (Anderson et al, 2019;Blanchard et al, 2017;Drummond et al, 2014;McCormack, 2014;Robinson et al, 2018;White & Hobson, 2017). However, there was evidence of increased levels of intentional touching in other settings (Brandth & Kvande, 2018;Magrath & Scoats, 2019;Scoats, 2017).…”
Section: Physicalitymentioning
confidence: 99%
“…The Global Theme of Inclusivity relates to the participants' acceptance of homosexuality, decreasing levels of homophobia, as well as decreasing levels of misogyny, and a general desire for gender equality. Twenty-four of the 33 studies reported that the participants displayed decreased levels of homophobia (Adams, 2011;Anderson, 2008Anderson, , 2011Anderson, , 2012Anderson et al, 2019;Anderson & McCormack, 2015;Anderson & McGuire, 2010;Blanchard et al, 2017;Caruso & Roberts, 2018;Drummond et al, 2014;Fine, 2019;Hall et al, 2012;Jarvis, 2013;Jóhannsdóttir & Gíslason, 2018;Magrath & Scoats, 2019;McCormack, 2011McCormack, , 2014Morales & Caffyn-Parsons, 2017;Morris & Anderson, 2015;Pfaffendorf, 2017;Roberts et al, 2017;Robinson et al, 2018;Scoats, 2017;White & Hobson, 2017). This ranged from what was described as shifting attitudes toward homosexuality (Jarvis, 2013), to the complete absence of homophobia (Morales & Caffyn-Parsons, 2017).…”
Section: Inclusivitymentioning
confidence: 99%
See 1 more Smart Citation